Learning Device Preparation Training and Mentoring Based on Independent Learning at MA MUQ Langsa: Pelatihan dan Pendampingan Penyusunan Perangkat Pembelajaran Berbasis Merdeka Belajar di MA MUQ Langsa - Ema Julianda; Weni Astari; Uci Dwi Cahya; Evi Zulida; Dede Gustian (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service activity aims to improve the ability of teachers to create complete learning administration materials in accordance with the current curriculum, namely Merdeka Belajar. The implementation of community service is carried out using training and mentoring methods. Training is carried out by providing an understanding of the preparation of complete learning administration materials. Mentoring is carried out in the activity of making learning administration. This training is a managerial training for homeroom teachers. After the activity was carried out, there was an increase in understanding of learning administration by 75%. The results of this community service activity are in the form of complete learning administration materials such as syllabus, prota, prosem, and RPS in accordance with the independent learning curriculum. The training participants (homeroom teachers) hope for the continuation of the program to improve teacher competence.